(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Familial hypocalciuric hypercalcemia (FHH) is a rare, usually benign, autosomal dominant disorder caused by mutations in the calcium-sensing receptor (CaSR) gene. It is typically characterized by mild, lifelong hypercalcemia, relative hypocalciuria, and normal or mildly elevated parathyroid hormone levels. Here we present a case of a 38-year-old male with newly diagnosed diabetes mellitus for 3 months who had recurrent episodes of acute pancreatitis for the last 1 year. Recurrent pancreatitis, a recognized complication of primary hyperparathyroidism, has rarely been reported on FHH, which made our case a unique one. Studying the case might help to develop insight into the diagnosis and management of this rare entity. [J Assoc Clin Endocrinol Diabetol Bangladesh, 2025;4(Suppl 1): S56]